Bioengineered Tumor‐Derived Extracellular Vehicles Suppressed Colorectal Cancer Liver Metastasis and Bevacizumab Resistance - Junjiang Wang; Chunsheng Liu; Ping Wang; Zhiyuan Liu; Weixian Hu; Zejian Lv; Chengzhi Huang; Xueqing Yao (Advanced Science)
Abstract Antiangiogenic therapies, such as bevacizumab, are among the causes of cancer‐related death in patients with colorectal cancer (CRC) with liver metastasis. Delivering siRNAs via primary cell originating from primary cells is a promising method for targeting CRC liver metastasis and drug resistance. Here, it is found that the expression of CCL24 is significantly upregulated in tumor tissues at the CRC liver metastasis site. In addition, CCL24 is significantly upregulated in tumor tissues from bevacizumab‐resistant patients. CCL24 promotes the formation of inflammatory tumor‐associated fibroblast subsets in the CRC liver metastasis microenvironment and induces resistance to bevacizumab therapy. Based on these results, a primary cell‐derived extracellular vehicle delivery system is designed for the simultaneous delivery of siRNAs targeting CCL24 in the tumor microenvironment (TME). Downregulation of CCL24 in the TME by delivering bioengineered extracellular vehicles significantly increased sensitivity to antiangiogenic therapy in a CRC mouse model. A novel therapeutic target is identified for patients with CRC with liver metastasis and suggested a possible therapeutic alternative for patients with CRC with resistance to antiangiogenic therapy and distant metastasis.